Клініко-психологічна структура емоційних порушень у хворих на полінаркоманію - Григорян, Артур Зоренович; Grygorian, A. Z. (My University, 2014)
Проаналізовано клініко-психологічну структуру емоційних порушень у хворих на полінаркоманію (опіоїди, канабіноїди, алкоголь, тютюн). Встановлено домінуючі емоції, визначено рівні реактивної та особистісної тривожності. Описано специфічний наркоманічний дефект за ознакою емоційних порушень, до якого входять, окрім формування тривожної особистості, емоційна диссоціація та спотворення самосприйняття адекватного емоційного стану. The article presents the analysis of clinical psychological patterns of emotional disorders in patients with poly-drug addiction (opioids, cannabinoids, alcohol, tobacco). Dominant emotions were determined; certain levels of state and trait anxiety were revealed. Specific drug-defect on the basis of emotional disorders, the structure of which, in addition to formation of anxiety personality, includes specific emotional dissociation and distortion of perception of adequate emotional state was described.
Clinical psychological structure of emotional disorders in patients with poly-drug addiction
Keywords: адикція; полінаркоманія; емоційні порушення; психоактивні речовини; addiction; poly-drug addiction; emotional disorders; psychoactive substances